Pengaruh Pendidikan Kesehatan Terhadap Peningkatan Pengetahuan Keluarga Tentang Perawatan Pasien Dengan Masalah Gangguan Persepsi Sensori Halusinasi Pendengaran - Tarigan, Almina Rospitaria; Saragih, Nurlela Petra; Munthe, Dewi Sartika; Silitonga, Lisbeth Laora; Saragih, Ruth Sarah Julfrida (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One form of mental disorder is hallucinations. Hallucinations are false or false perceptions but there is no stimulus that causes them or there is no object. In Indonesian mental hospitals, around 70% of the hallucinations experienced by mental patients are auditory hallucinations, 20% are visual hallucinations, and 10% are nasal, tasting and tactile hallucinations. A family is a group of two or more individuals who are bound by blood, marriage or adoption, and each family member always interacts with each other (Mubarak, 2009). The family is seen as a system, so mental disorders in one family member will disrupt all systems, or family conditions. This is a factor that causes mental disorders in family members. It can be concluded how important the role of the family is in the occurrence of mental disorders and the readjustment process after completing the treatment program. Therefore, family involvement in treatment is very beneficial to the patient's recovery process (Yosep, 2009). However, for serious illnesses or life-threatening illnesses, family crises can occur, where the family experiences brief chaos as a response to the force of the stressor. The research design used in this study was a pre-experimental design with a one-group pre-test post-test design. The characteristic of this research is that it reveals cause and effect relationships by involving a group of subjects. From the research results, it was found that the level of family knowledge before health education was carried out regarding the care of patients with sensory perception disorders, auditory hallucinations, most of the respondents were still lacking. The level of family knowledge after health education was carried out regarding the care of patients with auditory hallucinations problems increased compared to before health education. Apart from that, there is an influence of health education on increasing family knowledge about caring for patients with sensory perception disorders, auditory hallucinations.